Effect of Biochar and Inorganic Fertilizer on the Soil Properties and Growth and Yield of Onion (Allium cepa) in Tropical Ethiopia - Abreham Berta Aneseyee; Tekilil Wolde (The Scientific World Journal)
Biochar is a carbon-rich product, which is processed by pyrolyzing biomass to improve soil properties and maintain environmental sustainability. This study aim was to investigate the effect of biochar and inorganic fertilizer on soil properties, growth, and yield. Four treatments and four replications have been used for the experimental plots using Randomized Complete Block Design (RCBD). Soil physiochemical properties have been investigated based on soil samples within 0–30 cm depth in each plot. The two types of biochar (grass and chat waste) have been used for the treatments. The pyrolyzing temperature required for grass and chat waste is 250°C and 1100°C, respectively. The plant height, total yield, and the marketable and nonmarketable yield of onion have been examined. The analysis showed that treatment with grass biochar and inorganic fertilizer had a similar effect on soil properties but chat (Catha edulis) biochar had a lower effect on soil properties. The total yield and days to 70% maturity have been increased due to the cumulative treatment of grass biochar and inorganic fertilizer. The biochar of grass and inorganic fertilizer have been significantly increased in marketable bulb yield, but unmarketable yield becomes decreased. The chat waste and controlled treatments shown an increased unmarketable yield and declined marketable bulb yield. Overall, biochar can substitute the inorganic fertilizer, which can help to improve the w soil fertility and environmental sustainability. Therefore, biochar has a win-win solution.